Surface-confined heterometallic triads on the basis of terpyridyl complexes and design of molecular logic gates - Mondal, Prakash Chandra; Singh, Vikram; Jeyachandran, Yekkoni Lakshmanan; Zharnikov, Michael (ACS applied materials & interfaces, 2015)
Surface-confined heterometallic molecular triads (SURHMTs) were fabricated on SiOx-based solid substrates using optically rich and redox-active Fe-, Os-, and Ru-based terpyridyl complexes as metalloligands and Cu2+ ions as linkers. Optical and electrochemical studies reveal efficient electronic intramolecular communication in these assemblies. The UV-vis spectra of the triads exhibit a superposition of the metal-to-ligand charge-transfer bands of individual complexes, providing a significant enlargement of the optical window, useful for application. Similarly, cyclic voltammograms of SURHMT layers show a variety of redox peaks corresponding to individual complexes as well as multi-redox states at a low potential. Interaction of a representative SURHMT assembly with redox-active NOBF4 was investigated and used as a basis for configuring molecular logic gates.